INTERNATIONAL LEGAL REGULATION OF SOCIAL PROTECTION OF CHILDREN WHO HAVE SUFFERED AS A RESULT OF MILITARY ACTIONS AND ARMED CONFLICTS - Beluga, Julia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Children growing up in conflict zones are protected under international humanitarian law as part of the civilian population. However, due to their vulnerability and special developmental needs, children are entitled to special protection. Some guarantees provided for in international legal acts have become norms of customary law. Every child has the right to protection of their violated rights, guaranteed by both international and national standards. International standards are soft law instruments that guide to enhance protection and respect for children’s rights during military conflicts. The main international legal acts that form the basis for the protection of children’s rights during armed conflicts are: the UN Convention on the Rights of the Child (1989); Optional Protocol to the Convention on the Rights of the Child on the Involvement of Children in Armed Conflict (2000, was ratified by Ukraine in 2004); the Geneva Convention relative to the Protection of Civilian Persons in Time of War (1949) and several UN Security Council Resolutions adopted between 1999 and 2009. These are the norms of international humanitarian law, which in war conditions become a priority and provide not only for the general protection of the rights of children as part of the civilian population but also for special ones. And their main goal is, first of all, the protection of the civilian population, that is not directly in a military conflict (it does not have weapons in its hands). And it is precisely international humanitarian law that aims to protect them to do everything possible to minimize violence, which, unfortunately, is inherent in any military conflict. Purpose: to analyze international regulations on the social protection of children affected by military operations and armed conflicts. Methods: formal-logical method and method of system analysis, structurally functional method, and other research methods. Results: international legal acts regulating the social protection of children affected by military operations and armed conflicts were analyzed. Discussion: the issue is that there are mechanisms for recording violations and identifying those responsible, but they do not adequately prevent these events before they occur. Existing means of protecting children’s rights in times of war are often ineffective and not properly implemented, although they exist.